Facies analysis, foraminiferal record and chronostratigraphy of Holocene sequences from Saltés Island (Tinto-Odiel estuary, SW Spain): The origin of high-energy deposits. (5th March 2019) - González-Regalado, M.L.; Gómez, P.; Ruiz, F.; Cáceres, L.M.; Clemente, M.J.; Rodríguez Vidal, J.; Toscano, A.; Monge, G.; Abad, M.; Izquierdo, T.; Campos, J.M.; Bermejo, J.; et al.
Abstract: A multidisciplinary analysis of Holocene sediments from La Cascajera (Tinto-Odiel estuary, SW Spain) has allowed to differentiate five sedimentary facies (sandy tidal flat, clayey tidal flat, washover fan, salt marsh, edaphic horizon), according to their granulometric characteristics, internal structure, mineralogical composition, clay mineral assemblage and paleontological record. These data, coupled to 14 C AMS dating, suggest an evolution from a sandy tidal plain to a chenier before 2100 cal yr BP. This initial chenier was partially eroded later by regional storms between 2100 cal yr BP and 1900 cal yr BP, leading to the deposition of two washover fans. These facies have been eroded in the last centuries by the action of an ebb-tide channel. Graphical abstract: Image 1